Service Integration and Management (SIAM) Foundation Body of Knowledge (BoK) - Agutter, Claire (IT Governance Ltd, 2021)
Service Integration and Management (SIAM(tm)) Foundation Body of Knowledge (BoK), Second edition has been updated to reflect changes to the market and is the official guide for the EXIN SIAM(tm) Foundation certification. Prepare for your SIAM(tm) Foundation exam and understand how SIAM can benefit your organization!